2007
DOI: 10.2337/dc06-2272
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Oral Antihyperglycemic Therapy on All-Cause Mortality Among Patients With Diabetes in the Veterans Health Administration

Abstract: OBJECTIVE -The objective of this analysis was to evaluate the impact of several classes of oral antihyperglycemic therapy relative to sulfonylurea monotherapy on all-cause mortality among a cohort of patients with diabetes from the Veterans Health Administration (VHA). RESEARCH DESIGN AND METHODS-A retrospective cohort study using data obtained from the VHA Diabetes Epidemiology Cohort was used. Users of oral antihyperglycemic therapy were classified into the following cohorts: sulfonylurea monotherapy, metfor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
32
0
2

Year Published

2008
2008
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(35 citation statements)
references
References 23 publications
1
32
0
2
Order By: Relevance
“…It cannot be concluded from the literature whether combination therapy with metformin and SU has harmful effects, as indicated by the UKPDS (13,(25)(26)(27). At present, the international guidelines recommend combination therapy when monotherapy fails (4).…”
Section: Oral Hypoglycaemic Agentsmentioning
confidence: 83%
See 1 more Smart Citation
“…It cannot be concluded from the literature whether combination therapy with metformin and SU has harmful effects, as indicated by the UKPDS (13,(25)(26)(27). At present, the international guidelines recommend combination therapy when monotherapy fails (4).…”
Section: Oral Hypoglycaemic Agentsmentioning
confidence: 83%
“…Observational studies have yielded conflicting results of combined intervention with metformin and insulin secretagogues with respect to the risk of CVD (25,26). A recently published meta-analysis indicates an increased frequency of CVD by combined intervention with metformin and insulin secretagogues compared with diet or monotherapy (27).…”
Section: Metforminmentioning
confidence: 99%
“…Other observational data comparing sulphonylureas with metformin have also supported the observation that sulphonylureas are associated with a higher risk of mortality as a class [56][57][58], and glipizide, glimepriride, tolbutamide and glibenclamide specifically [59]. Conversely, a retrospective study using data from VHA Diabetes Epidemiology Cohort found that the risk of all-cause mortality was not significantly different for metformin monotherapy and sulphonylurea monotherapy [adjusted odds ratio (OR) 0.87; 95% CI 0.68-1.10] [60]. In addition, a meta-analysis of available data from randomized, controlled trials (RCTs) did not find that metformin had a statistically significant effect on all-cause mortality.…”
mentioning
confidence: 91%
“…1 These unexpected findings have been the subject of much debate, 2 and have led to the publication of several observational studies in recent years. [3][4][5][6][7][8][9][10][11] Despite the number of observational studies published to date, there is great discordance between their results. Whereas in some studies the use of the combination of sulfonylureas and metformin was associated with an increased risk of all-cause mortality, 3,5,8,11 others found no association, 6,9 while some found protective effects.…”
Section: Introductionmentioning
confidence: 99%
“…[3][4][5][6][7][8][9][10][11] Despite the number of observational studies published to date, there is great discordance between their results. Whereas in some studies the use of the combination of sulfonylureas and metformin was associated with an increased risk of all-cause mortality, 3,5,8,11 others found no association, 6,9 while some found protective effects. 4,7,10 A recent meta-analysis of these studies found that combination therapy of sulfonylur-eas and metformin significantly increased the risk of the composite endpoint of cardiovascular diseaserelated hospitalizations or mortality, but not for allcause mortality.…”
Section: Introductionmentioning
confidence: 99%